EVALUASI PERILAKU LALU LINTAS PADA SIMPANG DAN KOORDINASI ANTAR SIMPANG - Miftahul Fauziah; Raafi Widyaputra Yulianyahya; Rizki Budi Utomo (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2016)
Stasiun Brambanan and Taman Wisata Candi intersection are two short separate intersections around Prambanan Temple. The distance of these intersections is only 436 m, while the traffic volume is too high and because of no signal coordination between these intersections, they lead to traffic congestion during peak hour. Therefore, the need for improvement by using traffic signal coordination between them is significant. The traffic micro simulation software of VISSIM was used to simulate the existing delay and to design traffic signal coordination. To obtain existing traffic volume during peak hour and off peak hour period, and to design a new cycle time for signal coordination, primary data were compiled according to direct observation.Result showed that the existing traffic route generates travel time of 57.24 seconds and average traveling speed of 27.42 kilometer/hour with the service level of “E” in peak hour period. The best alternative of cycle time for peak hours was 117 seconds, with average delay of17.65 seconds, travel time between intersection was 50.99 seconds, average travel speed of30.78 kilometer/hour and the service level of “E”. Travel time from East leg at 1st intersection onto East leg at 2nd intersection (Yogya-Solo Routes) was 31.73 seconds, delay of 15.57seconds, average travel speed of 49.47 kilometer/hour with the service level of “E”. On off peak hour period, the existing average delay was 19.59 seconds, average travel time of 39,6 seconds and average speed of 39.64 kilometer/hour with the service level of “E”. The best alternative ofnew cycle time was 98 seconds, average delay of 16.42 seconds, travel time of 30.77 seconds, average travel speed 51.01 kilometer/hour, and the service level of “D”. Travel time from East leg at 1st intersection onto 2nd intersection was 27.25 seconds, delay of 14.83 seconds, average travel speed of 57.60 kilometer/hour with the service level of “D”. In general it can be said that the traffic coordination slightly increase traffic performance during peak hour at the same service level range, while on off peak hours it significantly improves their level of service.